The Relationship between Spousal Violence and Levels of Education: : An Analysis of the Zambia Demographic and Health Survey 2013/14 - Masaiti, Gift; Mapoma, Chabila C.; Sikwibele, Muyapekwa; Kasonde, Mwewa (International Journal of African Higher Education, 2022)
Domestic violence against spouses, especially women, is a serious human rights issue and a well-recognised global public health concern. While it is often attributed to low educational levels, research on this relationship has produced mixed results. This study investigated the association between domestic violence against women and education level, especially higher education, in Zambia. The data were sourced from the 2013-14 Zambia Demographic and Health Survey, which surveyed a nationally representative sample. A total of 11 778 women responded to the survey’s module on domestic violence. Given that the study was interested in domestic violence experiences perpetrated by spouses, the sample was restricted to currently married women. The results show that wives with a higher level of education than their husbands were more likely to experience different forms of domestic violence than those with a lower or the same educational level as their husbands. Women’s household wealth and age, the husband’s level of education, and spousal education differences were found to be significantly associated with domestic violence. It is thus concluded that increasing the educational level of both spouses could be effective in reducing domestic violence in Zambia. Key words: Levels of education, spousal violence, Demographic Health Survey